"It worked for manufacturing…!". Issue 1 (January 2015) - Maylor, Harvey; Turner, Neil; Murray-Webster, Ruth
Abstract This paper describes the application of an Operations Strategy (OS) approach to project-based operations (PBOs), defined as low to medium volume and medium to high variety operations. The OS approach has been extensively and beneficially used in high and medium volume operations. By examining the development of OS from its genesis in manufacturing operations, we identify four aspects of the OS approach — strategic intent, focus, fit and resource configuration. These elevate the discussion of how to configure resources to gain competitive advantage from PBOs, to the level of business leaders. The four aspects are then analysed in greater detail, with a view to determining the adaptations required for application in a PBO. The results of this engaged study indicate that the approach delivered significant new insight for the organisation involved in the study. The contributions of this paper are identified for both practice and theory. For practice we demonstrate an alternative to a reliance on standards and process compliance to an opportunity to gain competitive advantage from PBOs. For theory, we have extended OS into PBOs and provide a basis for future theory testing. We conclude that there is a significant opportunity for further practical and theory development through using an OS perspective.